IMPACT OF WEB DESIGN, ASSURANCE, CUSTOMER SERVICE AND BRAND IMAGE ON INTENTION TO ADOPT INTERNET BANKING AND CUSTOMER LOYALTY AT BANK CENTRAL ASIA (BCA) - Revin Prasetia; Tantri Yanuar Rahmat Syah (International Journal of Economics, Business and Accounting Research (IJEBAR), 2020)
The intention to use a product is one of the most important factors that must be considered by all companies to be able to make the product attractive and used by people. The purpose of this paper is to analyse, relation between Website Design, Assurance and Customer service towards Intention to adopt internet banking and Customer Service and Brand Image towards Customer Loyalty. A literature review was developed to prove that there are few factors related to intention to adopt internet banking and customer loyalty. Besides, the methodology related to intention to adopt internet banking and customer loyalty allows firms to know which factors are important to increase their customer intention and loyalties. This research proved that web design, customer service have an effect on intention to adopt internet banking and customer service and brand image have an effect on customer loyalty, but in this research, assurance have no effect on intention to adopt internet banking. This article was conducted on 111 respondents which located in DKI Jakarta with age range of under 25 years old to 35 years old. This research only addresses several variables namely Website Design, Assurance, Customer service, intention to adopt internet banking and customer loyalty. This is a replication model of a journal written by Rahi & Ghani (2018), this research conducted specifically on customers of Bank Central Asia (BCA) which helps Bank Central Asia to understand what factors are important to increase their number of customers to adopt their internet banking facility. Keywords: Website Design, Assurance, Customer Service, Brand Image, Intention to use a product and Customer Loyalty.